Radiological MRI Images in Spinal Tumor: a Serial Case Report - Darma Jupriadi Tampubolon; I Made Dwijaputra Ayusta; Dewa Gde Mahiswara S (Eduvest - Journal of Universal Studies, 2025)
Spinal cord tumors are uncommon neoplasms that pose significant clinical challenges due to their potential to cause progressive neurological deficits. These tumors may originate from the spinal cord parenchyma, meninges, nerve roots, or surrounding vertebral structures, and are classified by location as intramedullary, intradural extramedullary, or extradural. Although they represent a small fraction of central nervous system tumors, their impact on motor, sensory, and autonomic function can be profound. Magnetic Resonance Imaging (MRI) is the modality of choice for the assessment of lesions within the spinal canal, providing detailed information on lesion location, morphology, and compressive effects. Accurate imaging is essential for diagnosis, surgical planning, and optimizing patient outcomes. This case series describes three patients presenting with spinal tumors and associated neurological symptoms. The first case involves an 18-year-old female with progressive right-hand hemiparesis. MRI revealed an intradural intramedullary lesion at the C5–C6 level with an intramedullary syrinx, suggestive of hemangioblastoma, confirmed histologically by vascular proliferation and atypical cells. The second case is a 42-year-old male with chronic neck pain and left arm weakness for seven months. MRI showed an intradural extramedullary mass at C2–C3 and central disc protrusion, diagnosed histopathologically as cellular schwannoma. The third case features a 49-year-old female with paraparesis, lower back pain, urinary incontinence, and a history of cervical adenocarcinoma. MRI revealed an extradural metastatic mass at T7–T9 levels, suggestive of metastatic mass. MRI is the best imaging modality for evaluating and diagnosing patients with suspected spinal tumors.